Anxiety and fear of COVID‐19 among nursing students during the COVID‐19 pandemic: A descriptive correlation study. Issue 1 (20th May 2021) - Kuru Alici, Nilgun; Ozturk Copur, Ebru
Abstract: Purpose: The aim of this study was to assess current situations regarding anxiety and fear of coronavirus disease 2019 (COVID‐19) level among nursing students. Design and Methods: A descriptive correlation design was adopted. The sample consisted of 234 nursing students. Data were collected using sociodemographic form, Beck Anxiety Inventory (BAI), and Fear of COVID‐19 scale. Findings: The mean BAI score of the students was 26.56 ± 8.86 and Fear of COVID‐19 total score was 18.95 ± 7.00. A positive correlation between total scores of the BAI and Fear of COVID‐19. The results of this study reveal that anxiety and fear of COVID‐19 levels were high among nursing students. Practice Implications: These findings have underlined there is an urgent need for interventions to reduce anxiety and fear of COVID‐19 among nursing students.